Analisis Interaksi Audiens terhadap Konten Berita Internasional di Instagram ANTARA News: Pendekatan Mixed Methods pada Strategi Engagement Digital - Maria Septian Riasanti Mola (JURNALISTIK DAN MEDIA, 2025)
This study aims to analyze audience interaction patterns toward international news content published on the official Instagram account of ANTARA News. Unlike previous studies focusing on distribution strategies, this research emphasizes engagement analysis using a mixed-methods approach that combines quantitative data (likes, comments, hashtags) and qualitative data (caption and visual content analysis). The study employs a mixed-methods design, collecting quantitative data from posts uploaded in June 2025 and qualitative insights from five top-engagement posts. The results indicate that audience engagement levels positively correlate with the relevance of themes, visual clarity, and narrative depth in captions. These findings support Social Media Engagement Theory (van Doorn) and Media Convergence (Jenkins), highlighting the importance of interaction-based content management in shaping editorial direction and optimizing international news distribution strategies on digital platforms.